2018
DOI: 10.1371/journal.pone.0203279
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to visual working memory performance with practice and feedback

Abstract: Visual working memory capacity is estimated to be around 3–4 items, but on some trials participants fail to correctly report even a single item from the memory array. Such failures of working memory performance are surprisingly common, and participants have poor self-awareness of them. Previous work has shown that behavioral feedback can reduce the frequency of working memory failures, but the benefits of feedback disappeared immediately after it was taken away. Here, we tested whether extended practice with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 61 publications
(91 reference statements)
6
24
0
Order By: Relevance
“…Our results are also in line with the recent finding that visual perception is not optimal in KS patients (Kasse et al, 2019). Importantly, recent findings suggest that visual working memory functioning can be trained in healthy individuals (Adam & Vogel, 2018), and a recent report in KS patients suggested that optimization of working memory performance could be managed through chunking of new information (El Haj, Kessels, Urso, & Nandrino, 2018). It would therefore be of particular interest to study the training effects of chunking visual working memory information for rehabilitation in KS.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also in line with the recent finding that visual perception is not optimal in KS patients (Kasse et al, 2019). Importantly, recent findings suggest that visual working memory functioning can be trained in healthy individuals (Adam & Vogel, 2018), and a recent report in KS patients suggested that optimization of working memory performance could be managed through chunking of new information (El Haj, Kessels, Urso, & Nandrino, 2018). It would therefore be of particular interest to study the training effects of chunking visual working memory information for rehabilitation in KS.…”
Section: Discussionsupporting
confidence: 92%
“…WM practice can enhance the WM function too. The effects of WM practice are similar to that of WM training in two ways: an improved task performance (Adam and Vogel, 2018) and an enlarged P300 amplitude (McEvoy et al, 1998; Zhao et al, 2013). However, no studies have ever reported an increase in N160 magnitude after practice.…”
Section: Introductionmentioning
confidence: 75%
“…The closer one’s answer to the original orientation of the item, the greater the recall performance. Given that the forced-choice Adam and Vogel [ 15 ] task measured mean performance, we ultimately used a difference in mean effect sizes to compare and assess changes in precision over time. Additionally, we used Pearson’s correlation coefficient to look at test–retest reliability.…”
Section: Methodsmentioning
confidence: 99%